Systemic sarcoidosis with pituitary adenoma - Carbone,Roberto G; Penna,Daniele; Monselise,Assaf; Puppo,Francesco (Journal of Clinical Imaging Science)
Involvement of the nervous system with sarcoidosis is seen clinically in approximately 5-15% of cases. In most cases, lesions are localized to the leptomeninges and cranial nerves, and rarely to the pituitary gland, leading to endocrinologic abnormalities. We report on an original clinical case demonstrating the effectiveness of 18F-fluorodeoxyglucose positron emission tomography/computed tomography (FDG-PET/CT) scan in the diagnosis and monitoring of systemic sarcoidosis with probable pituitary involvement.